Impact of pH and application time of meta-phosphoric acid on resin-enamel and resin-dentin bonding. (February 2018) - Cardenas, A.F.M.; Siqueira, F.S.F.; Bandeca, M.C.; Costa, S.O.; Lemos, M.V.S.; Feitora, V.P.; Reis, A.; Loguercio, A.D.; Gomes, J.C.
Abstract: Purpose: To evaluate the immediate microshear resin-enamel bond strength (μSBS) and the immediate and 6-month microtensile bond strength (μTBS) and nanoleakage (NL) of the adhesive interface performed by different pHs of 40% meta-phosphoric acid (MPA) were compared with conventional 37% ortho-phosphoric acid (OPA) under different application times. Additionally, the enamel etching patterns were evaluated and the chemical/morphological changes induced by these differents groups were evaluated. Materials and methods: One hundred and ninety-eight extracted human molars were randomly assigned into experimental groups according to the combination of independent variables: Acid [37% ortho-phosphoric acid (OPA), 40% meta-phosphoric acid (MPA) at pHs of: 0.5, 1 and 2] and Application Time [7, 15 and 30 s]. Enamel-bond specimens were prepared and tested under μSBS. Resin-dentin beams were tested under μTBS tested immediately or after 6-months of water storage. Nanoleakage was evaluated using bonded-beams of each tooth/time-period. Enamel etching pattern and chemical and ultra-morphology analyses were also performed. The μSBS (MPa) data were subjected to a two-way repeated measures ANOVA (Acid vs. Application time). For μTBS, Acid vs application time vs storage time data were subjected to three-way ANOVA and Tukey's test (α = 0.05). Results: MPA pH 0.5 showed μTBS similar to OPA, independently of the application time on enamel (p>0.05) or dentin (p>0.05). OPA provided higher nanoleakage values than MPA (p = 0.003). Significant decreases in TBS and increases in NL were only observed for OPA after 6 months (p = 0.001). An increase in the application time resulted in a more pronounced etching pattern for MPA. Chemical analysis showed that dentin demineralized by MPA depicted peaks of brushite and octacalcium phosphate. MPA exposed less collagen than OPA. However, optimal results for MPA were dependent on pH/application time. Conclusion: The use of 40% meta-phosphoric acid with a pH of 0.5 is an alternative acid-etching agent for dentin and enamel bonding. Furthermore, the use of MPA preserves the resin-dentin interface over a 6-months period, due to presence of brushite and octacalcium phosphate and a reduced demineralization pattern. Graphical abstract: Highlights: Meta-phosphoric acid preserves the resin-dentin interface over a 6-months period. Meta-phosphoric acid is an alternative acid-etching agent for enamel and dentin. Meta-phosphoric acid decreased demineralization pattern.